CLINICAL IMPLICATION OF RETINAL NERVE FIBER LAYER SCHISIS AND MACULAR FLUORESCEIN LEAKAGE IN PRIMARY IDIOPATHIC EPIRETINAL MEMBRANE. Issue 12 (December 2022) - Kim, Jonghyun; Kim, Seong-Woo; Choi, Mihyun; Yun, Cheolmin; Oh, Jaeryung
Abstract : Supplemental Digital Content is Available in the Text. Preoperative macular leakage was associated with preoperative retinal nerve fiber layer schisis. Patients with macular leakage and retinal nerve fiber layer schisis showed worse postoperative best-corrected visual acuity than those without both factors. Abstract : Purpose: We evaluated the relationship between macular fluorescein leakage and retinal nerve fiber layer (RNFL) schisis and investigated the visual prognostic values after pars plana vitrectomy (PPV) and idiopathic epiretinal membrane removal. Methods: We analyzed the correlations between preoperative optical coherence tomography (OCT) parameters and macular leakage. The final best-corrected visual acuity and central macular thickness were compared according to the presence or absence of macular leakage and RNFL schisis. Results: In 80 eyes with idiopathic epiretinal membrane treated with PPV and membrane peeling, preoperative macular leakage was associated with the presence of preoperative RNFL schisis and inner nuclear layer microcysts. Eyes with both macular leakage and RNFL schisis showed worse postoperative best-corrected visual acuity than those without both factors. Conclusion: In the presence of macular fluorescein leakage and RNFL schisis, postoperative best-corrected visual acuity is worse, and improvements in the central macular thickness are greater than those in the absence of both factors.